Efficacy of citrulline supplementation to decrease the risk of pulmonary hypertension after congenital heart disease surgery. A local experience - Silvera Ruiz, Silene (2020)
Fil: Silvera Ruiz, Silene. Universidad Nacional de Córdoba. Centro de Investigaciones en Bioquímica Clínica e Inmunología (CIBICI); Argentina.